Vivipary in Hedychium elatum (Zingiberaceae) - Bhadra, Sreetama; Ghosh, Manosij; Mukherjee, Anita; Bandyopadhyay, Maumita (Phytotaxa, 2013)
Vivipary is a rare phenomenon in Zingiberaceae. In this article we report vivipary in the genus Hedychium for the first time.